PENGARUH MODEL PEMBELAJARAN SINEKTIK TERHADAP KREATIVITAS SISWA PADA MATERI MENGGAMBAR IMAJINATIF MENGENAI ALAM SEKITAR - Agustin, Devi; Julia, Julia; Subarjah, Herman (Jurnal Pena Ilmiah, 2017)
The general purpose of this research is to know the difference of creativity improvement of imaginative drawing between students who learn used the synoptic model and students who learn used the conventional model. The research's design is quasi experiment. The sample in this research is grade III student of SDN I Jemaras Lor as control class and SDN II Jemaras Kidul as experiment class. The researchÂ instruments include basic skills test, student's creativity test, observation format, questionnaire, and interview guide. Result of research with significance level of Î± = 0,05 that have do indicate that synoptic learning model and conventional model can increase student creativity significantly. Based on the U-test, it is known that the synoptic model is not significantly better than the conventional model on improve student's creativity. On the learning process, in general case the students give a positive response to study that use the synoptic model, it was seen in the questionnaire that has been collected. The factors that can support synoptic model's learning can be seen from the performance of teachers that give optimal learning start from planning, implementation, until the evaluation. In addition, there is a sense of fun and interest of students to learning. Furthermore the inhibiting factor is grouping of the students did not do heterogeneous.